Gravity's century from Einstein's eclipse to images of black holes - Cowen, Ron 1957- (Harvard University Press, 2019)
Ron Cowen offers a sweeping account of the century of experimentation that has consistently confirmed Einstein's general theory of relativity. He shows how we got from Eddington's pivotal observations of the 1919 eclipse to the Event Horizon Telescope, aimed at starlight wrapping around the black hole at our galaxy's center
Description based on online resource; title from PDF title page (publisher's Web site, viewed 24. Aug 2021)
Keywords: Einstein, Albert -- 1879-1955; Geschichte; SCIENCE / History; Astrophysics; General relativity (Physics); Gravitation; Gravity; Quantum theory; Gravitationstheorie; Schwarzes Loch; Relativitätstheorie